Therapeutic landscape: the pivotal role of outdoor environment in cultivating elderly well being - Mat Zin, Shaifudin; Zailan, Muhammad Khairi; Abu Bakar, Aniza (2013)
Globally, the rate of elderly population is expected to grow in great extent in the near future. In associates with their increasing of age, the health of elderly typically deteriorates, inducing the consequences of increased costs for caring and rehabilitation as the numbers of the elderly population grow. Thus, therapeutic landscape provides a distinctive and significant alternative in overcome these difficulties through associate them with natural environment. In this study, the author explored the effectiveness of therapeutic landscape and its surrounding environment with the elderly cognitive, emotional, social and physical condition in order to foster a healthy and active lifestyle of the community. The study was conducted in KompleksPenyayangBaktiSgBuloh and Dementia Home Care Kuala Langat. A thorough understanding about elderly impairments and illnesses as well as their outdoor environment and their elements will be identified in order to testify the prominence between these two mutual disciplinary. This research involved both observation and interview methods. Both of the techniques were used sequentially to get quantitative and qualitative data. The author used several assessments to confirm and to examine elderly behaviour patterns and their connection with the outdoor environment in cultivating health. Results obtained from the interview session with experts and professional involved with elderly shown their views on the possible benefits that a therapeutic landscape might have positive implications towards elderly and indirectly, it shall answer the research question. The data was then comprehensively analyzed in detail to outline a design recommendation in implementing an ideal outdoor environment for elderly.It is believed that the therapeutic landscape is effective and important in cultivating elderly health. Keywords: therapeutic, elderly, health, well being, outdoor environment